Konsep Guru Dalam Pandangan Ki Hajar Dewantara Dan Dari Perspektif Pendidikan Islam - Vera Nita, As’ad Badar, Ahmad Fuadi (Ability: Journal of Education and Social Analysis, 2023)
The background of this research was that one of the educational leaders who made a major contribution to education in Indonesia was Ki Hajar Dewantara. The educational thought put forward by Ki Hajar Dewantara has a nationalist character. This pattern is influenced by his mastery in the field of general education and his thinking which places more emphasis on teachers. Ki Hajar Dewantara's thoughts in the field of education give a distinctive style to education in Indonesia. The objectives of this research are: To find out the concept of the teacher in the view of Ki Hajar Dewantara and from the perspective of Islamic education. This study uses document library research design for data collection using documentation with work studies. The results of this study are that the teacher concept in Ki Hajar Dewantara's view is reflected in the mottos he has proclaimed, for example ing ngarso sung tulodo (if in front gives an example), ing madyo mangun karso (if in the middle gives encouragement), tut wuri handayani (if behind gives encouragement). There are also momong, among, ngemong. It has a meaning, namely that teachers can educate their students and how to care for them by giving positive values in their lives. Meanwhile, in the perspective of Islamic Education, teachers must also have two criteria, namely Alim and Fair. These two things form the basis because if a teacher is not a pious teacher, then he will have difficulty teaching because he does not know anything that can be conveyed to students. While fair here makes a teacher who can be imitated by students and become an example for them. Never mind what the teacher has taught, even what students see from their teacher will be remembered and become an example.